1965
DOI: 10.1172/jci105241
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Respiratory Frequency on Pulmonary Mechanics*

Abstract: In 1956 Otis and co-workers (1) compared the behavior of a single pulmonary pathway to an electrical circuit consisting of a capacitor and resistor in series with a sinusoidally varying voltage source. In a pulmonary pathway driven by a sinusoidally varying pressure, the resultant flow curve is also a sine wave and leads the pressure curve by an amount 9, which is determined by the relationship, O= tank ( 1/27rfRC), [1] where 9 is the phase angle in degrees between the pressure and flow curves, f is the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
4

Year Published

1969
1969
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 19 publications
2
13
0
4
Order By: Relevance
“…This variability could be due to different respiratory flows at the time of measurement or variability of upper airway area. f,, in the normal subjects was uniformly higher (P < 0.001) during inspiration compared to FRC (Table III) (16,50). A similar discrepancy was noted by DuBois et al (3) who attributed it to the failure of the lungs and chest wall to behave as a single, lumped system.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This variability could be due to different respiratory flows at the time of measurement or variability of upper airway area. f,, in the normal subjects was uniformly higher (P < 0.001) during inspiration compared to FRC (Table III) (16,50). A similar discrepancy was noted by DuBois et al (3) who attributed it to the failure of the lungs and chest wall to behave as a single, lumped system.…”
Section: Resultssupporting
confidence: 65%
“…Mead (11) considered the airways to be expanding structures in parallel with the air spaces, and using a two-compartment parallel model, showed that time-constant differences between the airways and the parenchyma caused frequency dependence of compliance and resistance. The fall in resistance and compliance predicted for normal subjects by Mead's model is too small to be apparent in measurements made at practical breathing frequencies, although there have been several reports of frequency-dependent compliance occurring in normal subjects (49)(50)(51). As peripheral airway resistance is increased, the time-constant differences between the airways and parenchyma become more prominent, and can account for most of the frequency-dependent behavior observed in diseased lungs without having to invoke a generalized distribution of peripheral time-constant discrepancies.…”
Section: Resultsmentioning
confidence: 98%
“…Previous reports on measurements of CGY. (l) as a function of frequency in "normal" subjects have noted several subjects whose lungs were frequency dependent (13,15,16). As Ingram and Schilder (13) point out in their series, the subjects who had frequency dependence were all cigarette smokers, and it is possible that they had disease in their small airways.…”
Section: Resultsmentioning
confidence: 98%
“…The compliance and resistance of the lungs have been shown to decrease as a function of ventilatory rate in normal subjects (2,6), and especially in subjects with obstructive lung disease (1, 3). Such rate-dependency ofcompliance and resistance may be explained by differences in the distribution offlow caused by either regional heterogeneities within the lungs (1, 4) or by the conducting airways acting as a "shunt" compliance in parallel with the peripheral airways (22).…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of the endotracheal tube was determined by fitting the pressure difference across the tube (calculated as the difference between the pressure proximal to the endotracheal tube and the tracheal pressure) to a similar equation in which the elastic term (DoVIC) was eliminated (8). The compliance of the chest wall (Cw ) was calculated from the compliances of the respiratory system (C RS ) and lungs (Cd as: (2) assuming that chest wall and lungs were dynamically in series (15). Eight breaths were analyzed for each ventilatory rate.…”
mentioning
confidence: 99%